Methods of Islamic Religious Education Teachers in Instruding Student Discipline Attitude - Yanuarti, Eka; Amelia Lestari, Reka Amelia Lestari; Komalasari, Bakti (International Journal of Education Research and Development, 2023)
This research is motivated by instilling student discipline through the PAI teacher method at SMA Negeri 3 Lebong. The problem that often occurs is that there are still many students who are less disciplined in going to school. The aims of this study were: (1) To find out the methods of PAI teachers in instilling discipline in students at SMA Negeri 3 Lebong. (2) To find out what are the inhibiting factors and supporting factors for PAI teachers in instilling discipline in students at SMA Negeri 3 Lebong. This research is field research (Field Research) that is descriptive and qualitative in nature. The subjects of this study were Islamic Religious Education Teachers at SMA Negeri 3 Lebong, and students at SMA Negeri 3 Lebong. Data collection techniques through observation, interviews, and documentation. Then the data analysis technique uses triangulation of sources and techniques (methods).